Effects of virgin coconut oil as adjunct therapy in the treatment of allergic rhinitis / Nazli Zainuddin, Nurul Azira Mohd Shah and Rosdan Salim - Zainuddin, Nazli; Mohd Shah, Nurul Azira; Salim, Rosdan (Faculty of Medicine, 2016)
Introduction: The role of virgin coconut oil in the treatment of allergic rhinitis is controversial. Thus, the aim of the present study is to determine the effects of virgin coconut oil ingestion, in addition to standard medications, on allergic rhinitis. We also studied the side effects of consumption of virgin coconut oil. Methods: Fifty two subjects were equally divided into test and control groups. All subjects received a daily dose of 10mg of loratadine for 28 days. The test group was given 10ml of virgin coconut oil three times a day in addition to loratadine. The symptoms of allergic rhinitis were scored at the beginning and end of the study. Results:, the symptom score were divided into nasal and non-nasal symptom scores. Sneezing score showed a significant difference, however the score was more in control group than test group, indicating that improvement in symptom was more in control group. The rest of the nasal symptom and non-nasal symptom score showed no significant difference between test and control groups. Approximately 58% of the test subjects developed side effects from consumption of virgin coconut oil, mainly gastrointestinal side effects. Conclusion: In the present study, ingestion of virgin coconut oil does not improve the overall and individual symptoms of allergic rhinitis, furthermore it has side effects